Ethics support in community care makes a difference for practice. (March 2018) - Magelssen, Morten; Gjerberg, Elisabeth; Lillemoen, Lillian; Førde, Reidun; Pedersen, Reidar
Background: Through the Norwegian ethics project, ethics activities have been implemented in the health and care sector in more than 200 municipalities. Objectives: To study outcomes of the ethics activities and examine which factors promote and inhibit significance and sustainability of the activities. Research design: Two online questionnaires about the municipal ethics activities. Participants and research context: A total of 137 municipal contact persons for the ethics project answered the first survey (55% response rate), whereas 217 ethics facilitators responded to the second survey (33% response rate). Ethical considerations: Based on informed consent, the study was approved by the Data Protection Official of the Norwegian Social Science Data Services. Findings: Around half of the respondents found the ethics project to have been highly significant for daily professional practice. Outcomes include better handling of ethical challenges, better employee cooperation, better service quality, and better relations to patients and next of kin. Factors associated with sustainability and/or significance of the activities were sufficient support from stakeholders, sufficient available time, and ethics facilitators having sufficient knowledge and skills in ethics and access to supervision. Discussion: This study shows that ethics initiatives can be both sustainable and significant for practice. There is a need to create regional or national structures for follow-up and develop more comprehensive ethics training for ethics facilitators. Conclusion: It is both possible and potentially important to implement clinical ethics support activities in community health and care services systematically on a large scale. Future ethics initiatives in the community sector should be designed in light of documented promoting and inhibiting factors.